MAKNA KARAKTER TARI TOPENG PAJEGAN DALAM AGAMA HINDU: The Meaning of Pajegan Mask Dance Characters in Hindu - Ni Wayan Lindawati Wayan; Dewa Gede Zanju Oktariana; I Nyoman Kiriana (Jurnal Pendidikan Agama, 2023)
The series of religious ceremonies certainly cannot be separated from the performance of the Pajegan mask dance, this dance presents a series of stories with different characters, where this dance is played by a man, playing the role of several characters in the story which are identical to the changing of masks in the story being staged. The appearance with the changes can be seen from the expression with changes in character and voice accompanied by dance movements that adapt to the role being performed. This dance is a wewali dance that is used as a complement to the religious gathering ceremony in Bali which is often known as the Pajegan Mask. The characters and shapes of the masks have different meanings and provide an inculcation of religious values and values about education in Hinduism